Atomic engineering of high-density isolated Co atoms on graphene with proximal-atom controlled reaction selectivity - Huan Yan (Nature Portfolio, 2018)
Controllable synthesis of single atom catalysts with sufficiently high metal loading remains challenging due to the tendency of agglomeration. Here the authors synthesize a series of stable atomically dispersed cobalt atoms on graphene with high Co loadings via the regeneration of active sites by atomic layer deposition.